HSV-1 alters lipid metabolism and induces lipid droplet accumulation in functionally impaired mouse dendritic cells - Mónica A. Farías; Felipe A. Cancino; Areli J. Navarro; Luisa F. Duarte; Abel A. Soto; Eduardo I. Tognarelli; Maximiliano J. Ramm; Bárbara N. Alarcón-Zapata; José Cordero; Sergio San Martín; Cristian Agurto-Muñoz; Angello Retamal-Díaz; et al. (iScience)
Summary: Herpes simplex virus type 1 (HSV-1) significantly impairs dendritic cell (DC) function, ultimately eliciting the death of these cells. Here, we sought to assess whether HSV-1 modulates lipid metabolism in mouse DCs as a mechanism of immune evasion. For this, we performed RT-qPCR gene arrays with ingenuity pathway analysis (IPA), RNA sequencing (RNA-seq) and gene set enrichment analysis (GSEA), confocal microscopy, transmission electron microscopy, ultra-high-performance liquid chromatography-quadrupole time-of-flight (UHPLC-QTOF) analysis, pharmacological inhibition of eight lipid-metabolism-related enzymes in HSV-1-infected DCs, co-cultures between virus-specific transgenic CD4+ and CD8+ T cells and HSV-1-infected DCs, and in vivo assays with mice. We found that HSV-1 significantly alters lipid metabolism in DCs and induces lipid droplet (LD) accumulation in these cells. Pharmacological inhibition of two particular lipid metabolism enzymes was found to partially restore DC function. Overall, these results suggest that lipid metabolism plays an important role in the impairment of DC function by HSV-1.